Pemberian Inhalasi Aromatherapy Lavender Mempengaruhi Nyeri Menstruasi Pada Remaja Putri - Irlinia, Rantika Resti; Susilawati, Susilawati; Astriana, Astriana; Evrianasari, Nita (Universitas Malahayati Bandar Lampung, 2022)
Background Menstrual pain is a medical condition that occurs during menstruation which causes pain in the abdomen and back that can bother daily activities, and it needs treatment. Lavender contains of antispasmodic and antivirus. Its nature is warm; pleasant oils that can reduce nervousness, anxiety, as well as lifting depression. Lavender includes very mild emmenagogue (smooth menstruation), chest tightness, pain after giving birth, vaginal discharge, periods during illness, pre-menstrual syndrome. Based on the results of a pre-survey which conducted in March 2019 at SMAN 14 Bandar Lampung, 36 adolescent girls experienced dysmenorrhea during menstruation. The purpose of this study is to know the Effect of Lavender Aromatherapy Inhalation on Menstrual Pain of Adolescent Girls at SMAN 14 Bandar Lampung in 2019.Methods This is quantitative research with pre-experimental method and one group pretest-posttes design approach. The population of this research are all adolescent girls in SMAN 14 Bandar Lampung. 43 adolescent girls who experience menstruation, but only 36 adolescent girls who meet the inclusion criteria are used as the sample of this research. In determining the sample, the researcher use purposive sampling. Then, T-test is used to analyze the data.Results showed that the average menstrual pain before the intervention was 5.44, the average menstrual pain after the intervention was 2.97.Conclusion the significance value was obtained p value 0,000 <(0.05). It means that there is an Effect of Lavender Aromatherapy Inhalation on Menstrual Pain of Adolescent Girls at SMAN 14 Bandar Lampung in 2019.Suggestion It is recommended for health workers, especially midwives to provide lavender aromatherapy as an alternative for easing adolescent girls' menstrual pain..Keywords: Menstrual Pain, Lavender Aromatherapy ABSTRAK Latar Belakang Nyeri menstruasi adalah kondisi medis yang terjadi pada saat haid atau menstruasi yang ditandai dengan nyeri atau rasa sakit di daerah perut dan panggung yang dapat mengganggu aktivitas sehari-hari dan memerlukan pengobatan. Kandungan lavender yaitu antispasmodic, antivirus, dan Sifat lavender termasuk hangat, minyak yang menyenangkan yang mampu mengurangi kegugupan, kecemasan, sekaligus mengangkat depresi. Lavender termasuk emmenagogue sangat ringan (melancarkan menstruasi), dada sesak, sakit setalah melahirkan, keputihan, periode selama sakit, sindrom pra-mentruasi. Berdasarkan hasil pre-survey yang dilakukan pada bulan Maret 2019 di SMAN 14 Bandar Lampung didapatkan 36 remaja putri mengalami disminorea pada saat menstruasi.Tujuan dari penelitian ini diketahui Pengaruh Pemberian Inhalasi Aromatherapy Lavender Terhadap Nyeri Menstruasi Pada Remaja Putri di SMAN 14 Bandar Lampung Tahun 2019.Metode Jenis penelitian kuantitatif, dengan rancangan penelitian metode pre eksperimen dengan menggunakan pendekatan one group pretest-posttes design. Populasi seluruh remaja putri di SMAN 14 Bandar Lampung sebanyak 43 remaja putri yang mengalami menstruasi, sample 36 remaja putri yang memenuhi kriteria inklusi.teknik pengambilan sampel purposive sampling, analisa data menggunakan uji T-Test.Hasil penelitian diketahui bahwa rata-rata nyeri menstruasi sebelum intervensi sebesar 5.44, rata-rata nyeri menstruasi sesudah diberikan intervensi sebesar 2,97, dan nilai signifikansinya didapatkan p value 0,000< a (0,05)Kesimpulan ada Pengaruh Pemberian Inhalasi Aromatherapy Lavender Terhadap Nyeri Menstruasi Pada Remaja Putri di SMAN 14 Bandar Lampung Tahun 2019.Saran bagi tenaga kesehatan khususnya bidan agar memberikan aromaterapi lavender sebagai salah satu alternative untuk penurunan nyeri menstruasi pada remaja putri. Kata Kunci : Nyeri Menstruasi, Aromaterapi Lavender